2014
DOI: 10.1111/psyp.12249
|View full text |Cite
|
Sign up to set email alerts
|

Energized by love: Thinking about romantic relationships increases positive affect and blood glucose levels

Abstract: We assessed the impact of thinking of a current romantic partner on acute blood glucose responses and positive affect over a short period of time. Participants in romantic relationships were randomly assigned to reflect on their partner, an opposite-sex friend, or their morning routine. Blood glucose levels were assessed prior to reflection, as well as at 10 and 25 min postreflection. Results revealed that individuals in the routine and friend conditions exhibited a decline in glucose over time, whereas indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…Love is not only rewarding, it may also boost energy and metabolic resources. For example, thinking about one’s romantic partner (vs. a friend or other control) increases positive affect and blood glucose levels (Stanton, Campbell, & Loving, 2014). …”
Section: Social Connection: Processes That Protect and Promote Healthmentioning
confidence: 99%
“…Love is not only rewarding, it may also boost energy and metabolic resources. For example, thinking about one’s romantic partner (vs. a friend or other control) increases positive affect and blood glucose levels (Stanton, Campbell, & Loving, 2014). …”
Section: Social Connection: Processes That Protect and Promote Healthmentioning
confidence: 99%
“…There are some other studies that were documented on the role of skin-to-skin contact and its relation to skin temperature which may show the connection between touch and skin temperature, to which we return when we discuss developmental thermoregulation. More indirect links have been provided between close relationships and the regulation of metabolic resources: Henriksen et al (2014) found that being socially integrated is related to a lesser consumption of drinks containing sugar during pregnancy, while thinking about a romantic partner (who is likely to be a source of warmth) leads to a slight increase in glucose levels ( Stanton et al, 2014 ). The first part of a research agenda on social thermoregulation should thus focus on uncovering the relationship between social integration, thermoregulation, and metabolism regulation in humans.…”
Section: Social Thermoregulation Saves Energy: Thermoregulation Acrosmentioning
confidence: 99%
“…Likewise, Stanton et al (2014) found that blood glucose levels increased when participants were asked to reflect upon their romantic relationships when compared with friend and routine control groups. This increase in blood glucose level was associated with positive affect as reported by participants.…”
Section: Introductionmentioning
confidence: 96%
“…It has been established that romantic love is a cultural universal, albeit not everyone in a given society can express it in the same way (Buss, 2006; Jankowiak, 2008; Jankowiak & Fischer, 1992). Accordingly, psychophysiological characteristics have been documented by evolutionary psychologists (e.g., Fisher, 2004; Loving, Crockett, & Paxson, 2009; Stanton, Campbell, & Loving, 2014) and efforts have been made to identify common cross-cultural characteristics. In 2009, de Munck, Korotayev, and Khaltourina launched a survey that discovered a “common core” in perceptions and ideologies regarding romantic love between the United States and Russia.…”
Section: Introductionmentioning
confidence: 99%